Functional capacity and physical activity level in failed back surgery syndrome patients - Lima,Malu Cristina de Araujo Montoro (2014)
BACKGROUND AND OBJECTIVES:Failed back surgery syndrome refers to a condition in which a patient has undergone back surgery with a poor outcome. This syndrome leads to losses in daily living activities and hinders the return to physical exercise. The objective of this study was to analyze the relation between chronic low back pain and functional capacity and the physical activity level of these patients.METHODS:Cross-sectional study comprising 57 patients, mean age 51.07±12.93 years, who underwent low back surgery. These patients were divided into two groups, according to the presence of chronic low back pain. All patients filled in a questionnaire that covered demographic data, visual analog scale for pain, Rolland-Morris Questionnaire to evaluate functional incapacity and International Physical Activity Questionnaire to measure physical activity level.RESULTS:The following predominated: women (77%), obese (49%), surgery for spinal disc herniation (80%), underwent one low back surgery (52%). Patients with chronic low back pain refer a greater perception of disability and 81% of this group showed an average of 3.53±3.51 points in Roland-Morris. Chronic low back pain had no influence on the different levels of physical activity demonstrated in patients with chronic low back pain and results of the International Physical Activity Questionnaire showed no significant difference between the groups (p=0.54).CONCLUSION:These findings indicate that there were other factors beyond chronic pain interfering with the physical activity level in these groups and further studies to explore lifestyle, physical exercise adherence and other dimensions of pain are still needed. Results contribute to the understanding and management of patients with chronic low back pain.